Benzydamine-An Affordable Over-the-Counter Drug with Psychoactive Properties-From Chemical Structure to Possible Pharmacological Properties - Bianca-Eugenia Ősz; George Jîtcă; Andreea Sălcudean; Carmen Maria Rusz; Camil-Eugen Vari (MDPI AG, 2023)
Benzydamine is a non-steroidal anti-inflammatory drug with distinct pharmacological properties from other compounds in the same therapeutic class. The differences are structural and pharmacological in nature; the anti-inflammatory mechanism is not strictly explained by the ability to interfere with the synthesis of prostaglandins. The compound is used strictly in local inflammatory diseases (inflammation in the oral and vaginal mucosa). In addition to the therapeutic indications found in the summary of product characteristics (SPC), the compound is used, in high doses, as a psychotropic substance for oral administration, having similar properties to lysergic acid diethylamide (LSD). As an over-the-counter (OTC) compound, it is easy to obtain, and the consequences of using it for purposes other than those assumed by the manufacturer raise various concerns. The reasons are related to the pharmacodynamic and pharmaco-toxicological properties, since neither the mechanism of action nor the possible side effects that would result from systemic consumption, in high doses, even occasionally, have been fully elucidated. The present review aims to analyze the pharmacodynamic properties of benzydamine, starting from the chemical structure, by comparison with structurally similar compounds registered in therapy (as an anti-inflammatory or analgesic) or used for recreational purposes.